FULFILLMENT OF PROTEIN NEEDS FROM PROCESSED OYSTER MUSHROOM BALLS (Pleurotus ostreatus) AND CELERY (Apium graveolens) AS A SOURCE OF PLANT PROTEIN - Rahmani, Putra; Hafizah, Ellyna; Putri, Rizky Febriyani (Transpublika Publisher, 2023)
The consumption of plant-based protein in Indonesia is comparatively higher than the consumption of animal-based protein, indicating a growing trend of substituting traditional meat-based ingredients with plant-based alternatives in dishes like meatballs. In order to address this shift and improve the nutritional value of the population's diet, researchers are exploring food diversification by incorporating oyster mushrooms and celery into meatball products. The objective of this study is to evaluate the impact of different ratios of oyster mushrooms (Pleurotus ostreatus) and celery (Apium graveolens) on the protein content and sensory qualities of plant-based meatballs. The research utilized a Randomized Complete Block Design (RCBD) with three different levels of celery addition in oyster mushroom meatballs: 0%, 10%, and 20%. Data analysis was conducted using SPSS software, employing the One-Way ANOVA test for normally distributed and homogenous data, and the Kruskal-Wallis test for non-normally distributed or heterogeneous data. The results indicated that the most favorable outcome was observed in formulation F2, which had a protein content of 9.700%, meeting the Indonesian National Standard for meatball products. Additionally, the addition of celery had a significant impact (p < 0.05) on the protein content.